2003
DOI: 10.1091/mbc.e02-10-0627
|View full text |Cite
|
Sign up to set email alerts
|

The AP-1 Clathrin-adaptor Is Required for Lysosomal Enzymes Sorting and Biogenesis of the Contractile Vacuole Complex inDictyosteliumCells

Abstract: Adaptor protein complexes (AP) are major components of the cytoplasmic coat found on clathrin-coated vesicles. Here, we report the molecular and functional characterization of Dictyostelium clathrin-associated AP-1 complex, which in mammalian cells, participates mainly in budding of clathrin-coated vesicles from the trans-Golgi network (TGN). The gamma-adaptin AP-1 subunit was cloned and shown to belong to a Golgi-localized 300-kDa protein complex. Time-lapse analysis of cells expressing gamma-adaptin tagged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 80 publications
8
50
0
Order By: Relevance
“…The interaction between ␥-adaptin and Rh50 is consistent with our previous study that demonstrated the role of AP-1 coat in the biogenesis of the CV (Lefkir et al, 2003). AP-1-coated vesicles could play an essential role in intracellular transport Journal of Cell Science 119 (5) Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The interaction between ␥-adaptin and Rh50 is consistent with our previous study that demonstrated the role of AP-1 coat in the biogenesis of the CV (Lefkir et al, 2003). AP-1-coated vesicles could play an essential role in intracellular transport Journal of Cell Science 119 (5) Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Deletion of the apm1 gene encoding the medium subunit of the clathrin adaptorprotein AP-1 also results in the absence of a characteristic CV (Lefkir et al, 2003). Together these results suggest that clathrin-coated vesicles, and more precisely AP-1 clathrincoated vesicles, are involved in the biogenesis of the CV.…”
Section: Introductionmentioning
confidence: 82%
“…We also generally observed in the disruption lines that stalks and spores were thin and smaller than those of the parental Ax2 cells. Interestingly, similar observations were observed in the AP-1 clathrinadaptor protein null cell development in Dictyostelium (Lefkir et al, 2003). These results suggest that VwkA may have physiological functions that are different from those of MHCK A, MHCK B, and MHCK C during development of D. discoideum.…”
Section: Vwka Gene Disruption Defectssupporting
confidence: 81%
“…All Dictyostelium cells used in this study were derived from the subclone DH1-10 (Cornillon et al, 2000) of the DH1 strain (Caterina et al, 1994). The 1 (Lefkir et al, 2003) and myoVII (Gebbie et al, 2004) knockout strains have been described previously. The myoK (Schwarz et al, 2000) knockout cells were a gift from T. Soldati (University of Geneva, Switzerland).…”
Section: Cells and Reagentsmentioning
confidence: 99%